2020
DOI: 10.1016/j.jflm.2020.102057
|View full text |Cite
|
Sign up to set email alerts
|

Sudden cardiac death after robbery: Homicide or natural death?

Abstract: Tako-Tsubo is one of a number of rare acquired cardiomyopathies that are characterized by left ventricular dyskinesia and symptomatology typical of acute myocardial infarction (AMI). The most important feature is that the clinical features are triggered by a severe physical or emotional stress. The authors describe the story of a woman, who was brutally assaulted by two men during a house robbery and died from sudden heart failure 8 hours later, after being taken to hospital. External examination revealed no m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…performed a myocardial biopsy on the day of admission of a 29‐year‐old woman with TTS and found neutrophilic infiltration in the myocardium 39 . Similar results were seen in several other autopsy cases 40,41 . In a histopathologic study, the myocardium of 25 patients who died of subarachnoid haemorrhage and 18 controls was stained with antibodies identifying neutrophil granulocytes (myeloperoxidase).…”
Section: Other Immune Cells In Ttssupporting
confidence: 60%
See 1 more Smart Citation
“…performed a myocardial biopsy on the day of admission of a 29‐year‐old woman with TTS and found neutrophilic infiltration in the myocardium 39 . Similar results were seen in several other autopsy cases 40,41 . In a histopathologic study, the myocardium of 25 patients who died of subarachnoid haemorrhage and 18 controls was stained with antibodies identifying neutrophil granulocytes (myeloperoxidase).…”
Section: Other Immune Cells In Ttssupporting
confidence: 60%
“… 39 Similar results were seen in several other autopsy cases. 40 , 41 In a histopathologic study, the myocardium of 25 patients who died of subarachnoid haemorrhage and 18 controls was stained with antibodies identifying neutrophil granulocytes (myeloperoxidase). The findings revealed that in the myocardium of subarachnoid haemorrhage patients, the number of myeloperoxidase‐positive cells was significantly higher than it was in controls.…”
Section: Other Immune Cells In Ttsmentioning
confidence: 99%
“…Given the intricate nature of scenarios related to viruses and the questionable histological cut-offs for infant death in myocarditis, this case demonstrates the need for an integrated and multidisciplinary approach, in order to understand the etiopathogenesis of sudden cardiac death, which can be extremely challenging, especially in the forensic scenario [ 23 - 25 ].…”
Section: Discussionmentioning
confidence: 99%